You That Read Wrong Again! A Transposed-Word Effect in Grammaticality Judgments - Mirault, Jonathan; Snell, Joshua; Grainger, Jonathan (Psychological Science, 2018)
We report a novel transposed-word effect in speeded grammaticality judgments made about five-word sequences. The critical ungrammatical test sequences were formed by transposing two adjacent words from either a grammatical base sequence (e.g., “The white cat was big” became “The white was cat big”) or an ungrammatical base sequence (e.g., “The white cat was slowly” became “The white was cat slowly”). These were intermixed with an equal number of correct sentences for the purpose of the grammaticality judgment task. In a laboratory experiment ( N = 57) and an online experiment ( N = 94), we found that ungrammatical decisions were harder to make when the ungrammatical sequence originated from a grammatically correct base sequence. This provides the first demonstration that the encoding of word order retains a certain amount of uncertainty. We further argue that the novel transposed-word effect reflects parallel processing of words during written sentence comprehension combined with top-down constraints from sentence-level structures.